![y'=(x^3+cx^2-2cx+8)'=3x^2+2cx-2c y'=(x^3+cx^2-2cx+8)'=3x^2+2cx-2c](https://tex.z-dn.net/?f=y%27%3D%28x%5E3%2Bcx%5E2-2cx%2B8%29%27%3D3x%5E2%2B2cx-2c)
Функция возрастает на всей числовой прямой, если
0" alt="y'>0" align="absmiddle" class="latex-formula"> для любых х.
0\\ \\ D=(2c)^2-4\cdot 3 \cdot (-2c)=4c^2+4c\cdot 6=4c(c+6)" alt="3x^2+2cx-2c>0\\ \\ D=(2c)^2-4\cdot 3 \cdot (-2c)=4c^2+4c\cdot 6=4c(c+6)" align="absmiddle" class="latex-formula">
![-6 -6](https://tex.z-dn.net/?f=-6%3Cc%3C0)
Откуда наименьшее целое значение -5.